Customer satisfaction of service quality : a comparison between Ar-Rahnu and conventional pawnbroking - Nur Rasyidah binti Kamaruzaman (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Pawnbroking institution is a place where the public can get instant cash, particularly among low-income earners. Some people prefer to get cash facility from pawnbroking institutions rather than formal financial institutions due to various reasons such as less stringent loan requirements and shorter time of loan approval. Customers only need to have valuable items to be pawned as a guarantee of the loan provided. In Malaysia, there are two types of pawnbroking service namely Islamic (Ar-Rahnu) and conventional. Conventional pawnbroking has been introduced in the community since 19th century, while the first Ar-Rahnu in Malaysia was established in 1992. As the capital required to set up pawnbroking institution is not very large, and in addition to a growing demand towards this service, the number of institutions offering pawnbroking is increasing year by year. This creates a stiff competition among the pawnbroking institutions in attracting customers. Customer satisfaction is, therefore an important indicator to determine the ability of the Ar-Rahnu institutions to sustain their businesses especially in the long run. This study aims to assess the level of customer satisfaction with regards to the service quality offered by the Ar-Rahnu and conventional pawnbroking institutions. It aims to identify if there are differences in the level of consumer satisfaction between Ar-Rahnu and conventional pawnbroking institutions. This study also identifies the dimension of service quality that affects the level of customer satisfaction. Five factors are evaluated namely: (i) reliability, (ii) responsiveness, (iii) assurance, (iv) empathy, and (v) tangibles. In methodology, the study adopts the survey method by distributing questionnaire to customers of the Ar-Rahnu and conventional pawnbroking institutions. A total of 300 samples were used and analysed through descriptive analysis, reliability analysis, independent t-test and linear regression analysis. The findings demonstrate that the level of customer satisfaction was higher in Ar-Rahnu compared to the conventional pawnbroking. Besides that, all factors evaluated in this study were found to give positive impact on customer satisfaction, both for Ar-Rahnu and conventional pawnbroking. Several recommendations to improve the quality service of Ar-Rahnu were proposed including (i) to extend operating hours, (ii) to open during weekend and public holiday, (iii) to put up notice if the institution is not in operation during its normal operating hours, and (iv) to improve the image of Ar-Rahnu to be more attractive and approachable.